Beneficial effect of a moderately energy-restricted diet on fibrinolytic factors in non-obese men - Velthuis-te Wierik, Erica J.M.; Meijer, Piet; Kluft, Cornelis; van den Berg, Henk (Metabolism, clinical and experimental, 1995)
Impaired fibrinolytic activity has been reported in the elderly and is thought to play a role in the etiology of cardiovascular disease, one of the leading causes of death in most Western countries. Since restriction of energy intake has been demonstrated to act beneficially on the aging process in a variety of species, we studied the effect of a 10-week moderately energy-restricted (ER) regimen (80% of habitual) on plasminogen activator inhibitor (PAl) activity, PAl-1 antigen, tissue plasminogen activator (tPA) activity, and tPA antigen in non-obese, middle-aged men. Moreover, the relationship between these fibrinolytic markers and glucose tolerance was investigated. Weight loss in the ER group (n = 16) was considerable (−7.4 ± 1.7 kg, P < .001). Subjects in the control group (n = 8) also lost some weight (−2.1 ± 1.5 kg, P < .01). Fasting glucose levels decreased in the ER group (−0.31 ± 0.48 mmol/L, P < .05), which was correlated with the extent of weight loss ( P < .01). Baseline insulin levels at 2 hours after an oral glucose load correlated with baseline PAl activity ( P < .001) and PAl-1 antigen levels ( P < .001). PAl activity decreased in the ER group (−2.94 ± 2.90 IU/mL, P < .001), particularly in subjects with a high baseline PAl activity (>9 IU/mL). Furthermore, energy restriction led to decreased PAl-1 antigen concentration ( P < .05), a nonsignificant increase in tPA activity, and a decrease in tPA antigen concentration ( P < .001). All these changes were more clear in subjects with a high baseline PAl activity: These results suggest that 10 weeks of moderate energy restriction has a profibrinolytic effect in non-obese, middle-aged men, at least in subjects with higher baseline PAl activity (>9 IU/mL). Moreover, in line with the suggestion that high PAl activity goes together with insulin resistance, a relationship between insulin concentration after a glucose load and PAl activity was found.